1990
DOI: 10.1007/bf00665594
|View full text |Cite
|
Sign up to set email alerts
|

Preference of cabbage white butterflies and honey bees for nectar that contains amino acids

Abstract: Amino acids occur in most floral nectars but their role in pollinator attraction is relatively unstudied. Nectars of butterfly-pollinated flower tend to have higher concentrations of amino acids than do flowers pollinated by bees and many other animals, suggesting that amino acids are important attractants of butterflies to flowers. In order to determine whether amino acids are important in attracting butterflies and bees, we tested the preference of cabbage white butterflies (Pieris rapae) and honey bees (Api… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
126
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(134 citation statements)
references
References 27 publications
2
126
0
Order By: Relevance
“…Members of Papilionidae and Pieridae more often visited NaCl rich sources and members of Nymphalidae, Hesperiidae and Lycaenidae preferred amino acid rich sources (Beck et al, 1999, Lai-Fook 1991, Pivnick & McNeil, 1987, Smedley & Eisner, 1995, 1996. In the present study results showed that the members of Papilionidae and Pieridae were preferred mineral sources as they did puddle on mostly water sources (mud, wet soil, wet sand, wet brick) while members of Nymphalidae, Hesperiidae and Lycaenidae were preferred to puddle on various nutrient sources (carrion, dung, rotten flowers) (Gilbert 1972, Alm et al, 1990, Erhardt & Rusterholz 1998, O'Brien et al, 2005. These results are indicated that butterfly requires various minerals and nutrients which are extracted through puddling for their reproductive success and physiological activities (Adler & Pearson, 1982, Pivnick & McNeil, 1987, Smedley & Eisner, 1996.…”
Section: Bank Of Bangshi Riversupporting
confidence: 53%
“…Members of Papilionidae and Pieridae more often visited NaCl rich sources and members of Nymphalidae, Hesperiidae and Lycaenidae preferred amino acid rich sources (Beck et al, 1999, Lai-Fook 1991, Pivnick & McNeil, 1987, Smedley & Eisner, 1995, 1996. In the present study results showed that the members of Papilionidae and Pieridae were preferred mineral sources as they did puddle on mostly water sources (mud, wet soil, wet sand, wet brick) while members of Nymphalidae, Hesperiidae and Lycaenidae were preferred to puddle on various nutrient sources (carrion, dung, rotten flowers) (Gilbert 1972, Alm et al, 1990, Erhardt & Rusterholz 1998, O'Brien et al, 2005. These results are indicated that butterfly requires various minerals and nutrients which are extracted through puddling for their reproductive success and physiological activities (Adler & Pearson, 1982, Pivnick & McNeil, 1987, Smedley & Eisner, 1996.…”
Section: Bank Of Bangshi Riversupporting
confidence: 53%
“…Female butterflies of some species prefer nectar sources containing amino acids (e.g. Alm et al, 1990;Erhardt and Rusterholz, 1998). One reason for this preference is that amino acids in nectar positively affect fecundity (Mevi-Schütz and Erhardt, 2005).…”
Section: Learning Rate Differences In Butterfliesmentioning
confidence: 99%
“…[42][43][44] Indeed, high AA concentrations have been reported for FNs from flowers that are adapted to pollinators such as butterflies, 8,9 flies 40 or bees, 45 and specific behavioral responses to AAs have been demonstrated for insect pollinators: butterflies and flies can detect single AAs in nectar sugar solutions 40,41 or showed preferences for nectar mimics containing specific mixtures of amino acids. 46 By contrast, nectarivorous birds were not found to prefer specific AAs in nectar solutions. 8,47,48 Variations in behavioral responses of nectar visitors to different AAs have also been shown for EFN.…”
Section: Secondary Metabolites and Vocs (Volatile Organic Compounds)mentioning
confidence: 97%